A dissection and angiographic study of anatomical variations in the anterior communicating artery complex in a South African sample - Madolo, Mbalentle (Department of Human Biology, 2025)
The anterior communicating artery complex (ACAC) consists of the A1 and A2 segments of the anterior cerebral artery (ACA) and the anterior communicating artery (ACoA). The ACAC is said to be the most frequent site of aneurysms and anterior cerebral circulation variations. Clear correlation between cerebral arterial circulation variations and aneurysm development has been reported. Cerebrovascular diseases play a significant role in the causes of morbidity in South Africa. South African data in this area of research is currently lacking and thus more knowledge is needed. This study aims to report the prevalence of variations in the ACAC and their link to the prevalence of cerebral aneurysms. For the dissection portion of this study, a total of 68 (35 female and 33 male) adult formalin fixed brains were included. These brains were from the bodies that were previously dissected in the Department of Human Biology, University of Cape Town by the medical undergraduate and honours post-graduate students. For the ang